Interaction between type 2 diabetes and past COVID-19 on active tuberculosis - Liz E. Calles-Cabanillas; Genesis P. Aguillón-Durán; Doris Ayala; José A. Caso; Miguel Garza; Mateo Joya-Ayala; America M. Cruz-Gonzalez; Raul Loera-Salazar; Ericka Prieto-Martinez; Javier E. Rodríguez-Herrera; Esperanza M. Garcia-Oropesa; John M. Thomas; et al. (BMC Infectious Diseases)
Abstract Background The global setback in tuberculosis (TB) prevalence and mortality in the post-COVID-19 era has been partially attributed to pandemic-related disruptions in healthcare systems. The additional biological contribution of COVID-19 to TB is less clear. The goal of this study was to determine if there is an association between COVID-19 in the past 18 months and a new TB episode, and the role played by type 2 diabetes mellitus (DM) comorbidity in this relationship. Methods A cross-sectional study was conducted among 112 new active TB patients and 373 non-TB controls, identified between June 2020 and November 2021 in communities along the Mexican border with Texas. Past COVID-19 was based on self-report or positive serology. Bivariable/multivariable analysis were used to evaluate the odds of new TB in hosts with past COVID-19 and/or DM status. Results The odds of new TB were higher among past COVID-19 cases vs. controls, but only significant among DM patients (aOR 2.3). The odds of TB in people with DM was 2.7-fold higher among participants without past COVID-19 and increased to 7.9-fold among those with past COVID-19. Conclusion DM interacts with past COVID-19 synergistically to magnify the risk of TB. Latent TB screening and prophylactic treatment, if positive, is recommended in past COVID-19 persons with DM. Future studies are warranted with a longitudinal design and larger sample size to confirm our findings.